Retinal detachment after cataract surgery : a population-based study - Thylefors, Joakim ; 0000-0003-0819-8683; Jakobsson, Gunnar; Zetterberg, Madeleine; Sheikh, Rafi ; 0000-0002-8289-9114 (Acta Ophthalmologica, 2022)
PURPOSE: To analyse the risk of rhegmatogenous retinal detachment (RRD) after cataract surgery, and to identify possible risk factors. METHOD: Observational cohort study of patients undergoing cataract surgery in Region Skåne, southern Sweden, during 2015-2017 were retrieved from the Swedish National Cataract Register. These were then cross-referenced with cases of retinal detachment surgery performed at the Skåne University Hospital in Lund from 2015 to 2020. The main outcome was RRD after cataract surgery. The influence of sex, age, axial length of the eye, rupture of the posterior capsule, patient comorbidity and other cataract complications were analysed. RESULTS: Among the 58 624 cases of cataract surgery, a total of 298 RRDs (0.51%) were identified up to the end of 2020. The mean time from cataract surgery to RRD was 667 days. The mean age was 65.3 years, compared to 74 years in the control group. A strong correlation was found between RDD and age: <60 years, incidence = 0.50%; 60-75 years, incidence = 0.14%; and >75 years, incidence = 0.04%. The correlation with axial length was also very strong: mean value 23.73 mm in those without RRD, and 25.13 mm in those with RRD (p < 0.001). Sex was also strongly correlated to RDD; 68.8% of cases of RRD being men. Among men younger than 60 years of age, with an axial length ≥25 mm, 9.46% exhibited RRD within the follow-up period (mean 4.7 years). Rupture of the posterior capsule was found in 2.01% of RRD patients compared to 0.74% in the control group. Diabetes, glaucoma or pseudoexfoliation had no impact on the prevalence of RRD. CONCLUSIONS: The three main risk factors for RRD following cataract surgery were found to be sex, age and axial length. The highest incidence of RRD (9.46%) were identified among men younger than 60 years of age and an axial length ≥25 mm.